Community Participation In Rural Tourism Development: TheExperience Of Wanayasa, Purwakarta - Gunawijaya, Jajang; Gulfira Akbar, Poeti Nazura; Pratiwi, Annisa (UI Scholars Hub, 2016)
Rural tourism has been quite a favourite form of alternative tourism in Indonesia over the last few years. Beeton (2006) defined rural tourism as a various activities that take place in nonurban settings, ranging from natural or manmade attractions, amenities and facilities, transportation, marketing to information system. People want to experience the indigenous culture and natural environment that settled in rural landscape. Many scholars have argued that the success of tourism development in rural areas depends on the collaboration in Indonesia using a case study of Wanayasa, Purwakarta. It assesses the level of community participation, limitations to community participation in tourism development and community’s commitment to participate in rural tourism development. To accomplish the main objective of this study, the qualitative approach was chosen as a research method. Primary data were collected through in-depth interviews and focus group discussion with 21 informants selected which comprises representation from 3 different group namely local authorities in Purwakarta region, representative of local community, tourism institution.. The data were analysed using qualitative content analysis to set priorities and alternative strategies. The results of this study indicated that local people is highly enthusiastic about tourism development in Wanayasa. Community’s commitment to participate in the rural tourism development is to contribute to the provision of access and infrastructure, organize cultural events, and preserve both cultural and natural environment independently. Local community is also interested in building mutual partnership to develop tourist destination, build businesses and promote its tourism to potential markets. However, the level of community involvement in Wanayasa is still at the stage of participation with material incentives and functional participation. While limitations of cultural, structural and operational are also challenges that must be anticipated, to bear on society engagement and mobilization in the development of tourism.